PENGARUH BUDAYA ORGANISASI TERHADAP KEPEMIMPINAN DAN KINERJA KARYAWAN PEMERINTAH KABUPATEN-KABUPATEN DI MADURA - Iriani Ismail (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
One of big problems for almost all regions in this autonomy era lately is about quality and quantity which less and scarce on human resources in a region. Concerning those problem, the development of human resources become crucial object to be described in this research.The study was an research which explain causality relation in many variables that study, these blue print research include in prediction classification examine and explain. The data collected by polling to gather primary data, beside that also done by interview with respondent directly. These research analisys unit are the employees of Pemerintah Kabupaten-kabupaten at Madura. This research respondent were focused on structural official functionary IIb and IIa inside Pemerintah Kabupaten-kabupaten at Madura with one hundreds and fifty samples.The result of contribution theory by Structural Equation Modelling (SEM) analisys is to search empirical evidence that the organizational cultureis not significantly influence toward leadership. Empirically this research is also found evidence that Organizational Culture influence toward employee performance. Next, leadership influence toward employee performance.